Sodium taurocholate cotransporting polypeptide (SLC10A1) deficiency: Conjugated hypercholanemia without a clear clinical phenotype. Issue 1 (25th August 2014) - Vaz, Frédéric M.; Paulusma, Coen C.; Huidekoper, Hidde; de Ru, Minke; Lim, Cynthia; Koster, Janet; Ho‐Mok, Kam; Bootsma, Albert H.; Groen, Albert K.; Schaap, Frank G.; Oude Elferink, Ronald P. J.; Waterham, Hans R.; et al.
<x xml:space="preserve">Abstract</x> The enterohepatic circulation of bile salts is an important physiological route to recycle bile salts and ensure intestinal absorption of dietary lipids. The Na+‐taurocholate cotransporting polypeptide SLC10A1 (NTCP) plays a key role in this process as the major transporter of conjugated bile salts from the plasma compartment into the hepatocyte. Here we present the first patient with NTCP deficiency, who was clinically characterized by mild hypotonia, growth retardation, and delayed motor milestones. Total bile salts in plasma were extremely elevated (up to 1, 500 μM, ref. <16.3) but there were no clinical signs of cholestatic jaundice, pruritis, or liver dysfunction. Bile salt synthesis and intestinal bile salt signaling were not affected, as evidenced by normal plasma 7α‐hydroxy‐4‐cholesten‐3‐one (C4) and FGF19 levels. Importantly, the presence of secondary bile salts in the circulation suggested residual enterohepatic cycling of bile salts. Sequencing of the SLC10A1 gene revealed a single homozygous nonsynonymous point mutation in the coding sequence of the gene, resulting in an arginine to histidine substitution at position 252. Functional studies showed that this mutation resulted in a markedly reduced uptake activity of taurocholic acid. Immunofluorescence studies and surface biotinylation experiments demonstrated that the mutant protein is virtually absent from the plasma membrane. Conclusion: We describe the identification of NTCP deficiency as a new inborn error of metabolism with a relatively mild clinical phenotype. The identification of NTCP deficiency confirms that this transporter is the main import system for conjugated bile salts into the liver but also indicates that auxiliary transporters are able to sustain the enterohepatic cycle in its absence. (Hepatology 2015;61:260–267)